On the uniqueness of non-reducible multi-player control problems. (2nd November 2021) - Karl, Veronika; Pörner, Frank
ABSTRACT: In this article, we consider a special class of generalized Nash equilibrium problems that cannot be reduced to a single player control problem. We find a sufficient condition, that proves the existence and uniqueness of solutions. Problems of this type can be solved by a semi-smooth Newton method. Applying the same condition as needed for the uniqueness of solutions, we derive superlinear convergence for the associated Newton method and the equivalent active-set method. We also provide detailed finite element discretizations for both methods. Numerical examples are presented to support the theoretical findings.